1 Assignment 5
3 Types and OCAML
4 ---------------
6 0. Recall that the S combinator is given by \x y z. x z (y z).
7    Give two different typings for this function in OCAML.
8    To get you started, here's one typing for K:
10     # let k (y:'a) (n:'b) = y;;
11     val k : 'a -> 'b -> 'a = <fun>
12     # k 1 true;;
13     - : int = 1
16 1. Which of the following expressions is well-typed in OCAML?
17    For those that are, give the type of the expression as a whole.
18    For those that are not, why not?
20     let rec f x = f x;;
22     let rec f x = f f;;
24     let rec f x = f x in f f;;
26     let rec f x = f x in f ();;
28     let rec f () = f f;;
30     let rec f () = f ();;
32     let rec f () = f () in f f;;
34     let rec f () = f () in f ();;
36 2. Throughout this problem, assume that we have
38     let rec omega x = omega x;;
40    All of the following are well-typed.
41    Which ones terminate?  What are the generalizations?
43     omega;;
45     omega ();;
47     fun () -> omega ();;
49     (fun () -> omega ()) ();;
51     if true then omega else omega;;
53     if false then omega else omega;;
55     if true then omega else omega ();;
57     if false then omega else omega ();;
59     if true then omega () else omega;;
61     if false then omega () else omega;;
63     if true then omega () else omega ();;
65     if false then omega () else omega ();;
67     let _ = omega in 2;;
69     let _ = omega () in 2;;
71 3. The following expression is an attempt to make explicit the
72 behavior of `if`-`then`-`else` explored in the previous question.
73 The idea is to define an `if`-`then`-`else` expression using
74 other expression types.  So assume that "yes" is any OCAML expression,
75 and "no" is any other OCAML expression (of the same type as "yes"!),
76 and that "bool" is any boolean.  Then we can try the following:
77 "if bool then yes else no" should be equivalent to
79     let b = bool in
80     let y = yes in
81     let n = no in
82     match b with true -> y | false -> n
84 This almost works.  For instance,
86     if true then 1 else 2;;
88 evaluates to 1, and
90     let b = true in let y = 1 in let n = 2 in
91     match b with true -> y | false -> n;;
93 also evaluates to 1.  Likewise,
95     if false then 1 else 2;;
97 and
99     let b = false in let y = 1 in let n = 2 in
100     match b with true -> y | false -> n;;
102 both evaluate to 2.
104 However,
106     let rec omega x = omega x in
107     if true then omega else omega ();;
109 terminates, but
111     let rec omega x = omega x in
112     let b = true in
113     let y = omega in
114     let n = omega () in
115     match b with true -> y | false -> n;;
117 does not terminate.  Incidentally, `match bool with true -> yes |
118 false -> no;;` works as desired, but your assignment is to solve it
119 without using the magical evaluation order properties of either `if`
120 or of `match`.  That is, you must keep the `let` statements, though
121 you're allowed to adjust what `b`, `y`, and `n` get assigned to.
123 [[Hint assignment 5 problem 3]]
125 4. Baby monads.  Read the lecture notes for week 6, then write a
126    function `lift` that generalized the correspondence between + and
127    `add`: that is, `lift` takes any two-place operation on integers
128    and returns a version that takes arguments of type `int option`
129    instead, returning a result of `int option`.  In other words,
130    `lift` will have type
132      (int -> int -> int) -> (int option) -> (int option) -> (int option)
134    so that `lift (+) (Some 3) (Some 4)` will evalute to `Some 7`.
135    Don't worry about why you need to put `+` inside of parentheses.
136    You should make use of `bind` in your definition of `lift`:
138     let bind (x: int option) (f: int -> (int option)) =
139       match x with None -> None | Some n -> f n;;